Integro-differential equations with multivalued solutions - Plotnikov, A. V.; Tumbrukaki, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We prove a theorem on the unique existence of a classical solution of an integro-differential equation with Hukuhara derivative. We also justify an averaging scheme for equations of this type in the standard form.